1993
DOI: 10.1093/carcin/14.9.1795
|View full text |Cite
|
Sign up to set email alerts
|

Differential binding of chromium(VI) and chromium(III) complexes to salmon sperm nuclei and nuclear DNA and isolated calf thymus DNA

Abstract: The binding of CrCl3.6H2O, Cr(NO3)3.9H2O, [Cr(L-His)2] (NO3)3.H2O, [Cr(L-Cys)(L-His)].3.5H2O, [Cr(L-His)(D-Pen)].H2O, Na[Cr(L-Cys)2].2H2O, K2[Cr(GS)2].3H2O, Na2-CrO4.4H2O, and Na2Cr2O7.2H2O to salmon sperm nuclei and nuclear DNA was determined. The Cr(III)-amino acid complexes and Cr(VI) exhibited significantly lower Cr-nuclei and Cr-DNA binding levels relative to the inorganic complexes CrCl3.6H2O and Cr(NO3)3.9H2O. The binding of CrCl3.6H2O, Cr(NO3)3.9H2O and Na2Cr2O7.2H2O to salmon sperm nuclei and nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 0 publications
3
26
0
Order By: Relevance
“…1, A and B, r ϭ 2). Our observations are consistent with other spectroscopic studies that showed no major Cr(VI)-DNA interaction in vitro in the absence of reducing agents (5,8,30). However, in the presence of metabolizing system, where Cr(VI) is reduced to Cr(III), major Cr(III)-DNA complexation has been observed (5,8,10,11).…”
Section: Resultssupporting
confidence: 92%
“…1, A and B, r ϭ 2). Our observations are consistent with other spectroscopic studies that showed no major Cr(VI)-DNA interaction in vitro in the absence of reducing agents (5,8,30). However, in the presence of metabolizing system, where Cr(VI) is reduced to Cr(III), major Cr(III)-DNA complexation has been observed (5,8,10,11).…”
Section: Resultssupporting
confidence: 92%
“…The lymphocytes that were treated with Cr(III) showed no measurable DNA repair, even in the presence of vitamin C or catalase, the anti-oxidant reagents that prevent the extent of DNA migration. Although our results with cationic Cr(III) species are in accord with the literature outlined previously, [Cr(L-his) 2 ]NO 3 · H 2 O reportedly displays lower binding (Hneihen et al, 1993), while a negatively charged Cr(III)-saccharide complex cleaved the PSV neoplasmid (Rao et al, 1994). Obviously, further research is needed to clarify the mechanism of DNA damage.…”
Section: +supporting
confidence: 91%
“…1 and 2), it was deduced that Cr(VI), 1, 3, and 4 generated no observable damage above the biologically realistic levels. The following experiments were therefore continued with the active species (Cr 3+ (aq) and 2) toward physiological concentrations, considering the values that were applied in previous studies ranging from 0.1 mM to 3.0 mM (Luo et al, 1996;Tsou et al,1999;Capellmann and Bolt, 1992;Hneihen et al, 1993;Standeven and Wetterhahn, 1991;Stearns and Wetterhahn, 1997). Ascorbate is also present in millimolar concentrations in cellular systems (Horning, 1975).…”
Section: Effect Of Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin has a high affinity for the nucleus (and possibly DNA itself), which may contribute to its protective effect against Cr-induced formation of 8-OH-dG. Cr(III) accumulates in nuclei and has a high affinity for DNA (52). Melatonin may prevent the formation of 8-OH-dG by displacing Cr(III) from the Cr-DNA binding complex and thereby reduce H202-mediated 'OH generation in the vicinity of DNA.…”
Section: Resultsmentioning
confidence: 99%